Breastfeeding among South Sudanese refugees in protracted settlements in Adjumani district, Uganda: facilitators and barriers - Christine N. Walters; Hasina Rakotomanana; Joel J. Komakech; Margaret Kabahenda; Jillian M. Joyce; Deana A. Hildebrand; Lucia Ciciolla; Barbara J. Stoecker (BMC, 2023)
Abstract Background Evidence suggests that forced migration and refugee status may adversely impact mothers' breastfeeding choices. Furthermore, suboptimal breastfeeding practices have been reported among vulnerable populations including those living in refugee settlements. Therefore, this study investigated the barriers and facilitators of breastfeeding in protracted settlements in Adjumani district, in the West Nile region in Uganda. Methods This study was conducted among refugees living in protracted settlements located in Uganda in July 2019. Participants, originally from South Sudan, included mothers (n = 63) and fathers (n = 32) of children less than 24 months of age. Agojo, Ayilo-I, and Nyumanzi were randomly selected among the 17 refugee settlements in Adjumani. Participants formed a total of six focus group discussions (FGDs); four FGDs for mothers and two FGDs for fathers. Each FGD consisted of 15-16 participants. Data were transcribed verbatim and back-translated into English. Thematic analysis was used and data were analyzed using NVivo, v. 12. Results Facilitators of breastfeeding included knowledge of breastfeeding benefits, support from husband/father, support from the community, and support from non-governmental organizations. Mothers and fathers noted that breastfeeding protected children from diseases and breastfed children grew well. Fathers, the community, and organizations provided material support for breastfeeding mothers. Four themes were identified as barriers to breastfeeding: physical, socioeconomic, knowledge, and psychosocial. Mothers and fathers described physical barriers such as mothers stop breastfeeding when they are sick or they feel they are not producing enough breastmilk. Mothers reported that working or educated mothers may use other milk to feed their infant. Some mothers and fathers believed infants under six months needed more than breastmilk. Fathers described psychosocial barriers such as mothers' fear of pain during breastfeeding and maternal mental health issues. Conclusion Interventions and policies that aim to improve breastfeeding in protracted settlements should consider addressing the barriers to breastfeeding at each level: physical, socioeconomic, knowledge, and psychosocial. Involving and encouraging support from husbands/fathers, relatives, and the community may increase adherence to breastfeeding recommendations.